Post-recovery experience among COVID-19 patients: A population-based online survey in India - Nitin Joseph; Prithvi Rajgopal; Paras Chaudhary; Ananya; Shreya Jain; Harish Yadav; Prajwal Kulkarni (Journal of Infection in Developing Countries)
Introduction: Patients who recovered from the acute phase of COVID-19 experience several post-COVID-19 health and social problems. This study was therefore done to explore the living experiences and the various health problems experienced by people and their determinants during the post-recovery phase of COVID-19.